2015
DOI: 10.1016/j.jare.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells regenerate infracted myocardium with neovascularisation development

Abstract: We achieved possibility of isolation, characterization human umbilical cord blood endothelial progenitor cells (EPCs), examination potency of EPCs to form new blood vessels and differentiation into cardiomyoctes in canines with acute myocardial infarction (AMI). EPCs were separated and cultured from umbilical cord blood. Their phenotypes were confirmed by uptake of double stains dioctadecyl tetramethylindocarbocyanine-labeled acetylated LDL and FITC-labeled Ulex europaeus agglutinin 1 (DILDL-UEA-1). EPCs of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…These cells are bone marrow-derived and can be mobilized in response to vascular injury or an inflammatory stimulus (Asahara et al, 1999; Shintani et al, 2001). Since 1997, there have been a plethora of studies reporting their vasculogenic, angiogenic and vascular repair properties (Abd El Aziz et al, 2015; Yu et al, 2016; Chilla et al, 2018; Kong et al, 2018). In vascular disease states and in advancing age, circulating EPC number and function are lower (Fadini et al, 2006; Thijssen et al, 2006; Xia et al, 2012;Liao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These cells are bone marrow-derived and can be mobilized in response to vascular injury or an inflammatory stimulus (Asahara et al, 1999; Shintani et al, 2001). Since 1997, there have been a plethora of studies reporting their vasculogenic, angiogenic and vascular repair properties (Abd El Aziz et al, 2015; Yu et al, 2016; Chilla et al, 2018; Kong et al, 2018). In vascular disease states and in advancing age, circulating EPC number and function are lower (Fadini et al, 2006; Thijssen et al, 2006; Xia et al, 2012;Liao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Histopathology showed increased neo-vascularization and immunostaining showed presence of EPCs newly differentiated into cardiomyocyte-like cells. These findings suggested that hEPCs can mediate angiogenesis and differentiate into cardiomyocytes in canines with AMI ( 16 ).…”
Section: Discussionmentioning
confidence: 93%
“…15 Normal feeding is extraordinarily important for the first 4 weeks after surgery because it can help to form a fibrous cap and the lipid core, similar to the human atherosclerotic plaque. 16…”
Section: Discussionmentioning
confidence: 99%